HUBUNGAN AKTIVITAS FISIK DAN TINGKAT KECEMASAN DENGAN GANGGUAN SIKLUS MENSTRUASI PADA MAHASISWI - Muslimahtun Baadiah; Sri Winarni; Atik Mawarni; Cahya Tri Purnami (Jurnal Kesehatan Masyarakat (Undip), 2021)
Menstrual cycle disorders experienced by adolescents aged 15-24 years need to be vigilant because the disorder can indicate ovulation or infertility problems and anemia. The purpose of the study was to analyze the relationship of physical activity and anxiety levels with menstrual cycle disorders. This research is quantitative research with cross sectional study methods. The population in this study was 346 second semester students with a sample of 83 students. Sample determination using a simple random sampling method. Data collection using polls distributed through google form. Data analysis was conducted univariate and bivariate through pearson product moment correlation test. The results of this study showed that most of the respondents were 19 years old and from Java. Most respondents had menstrual disorders (85.5%), physical activity in the mild category (53.0%) and experienced mild levels of anxiety (60.2%). Correlation test results showed a weak positive relationship between physical activity variables and menstrual cycle disorders (p value=0.032 r=0.236), but anxiety levels were not associated with menstrual cycle disorders (p value=0.613 r=-0.056). The conclusion is that there is a weak positive relationship between mild physical activity and menstrual cycle disorders (p value = 0.032, r=0.236). It is recommended that students increase physical activity with routine. For example doing running, aerobic exercise, cycling and swimming.